2019
DOI: 10.1093/mnras/stz1699
|View full text |Cite
|
Sign up to set email alerts
|

The retrograde orbit of the globular cluster FSR1758 revealed with Gaia DR2

Abstract: We report the first radial velocity measurements of the recently identified globular cluster FSR1758. From the two member stars with radial velocities from the Gaia Radial Velocity Spectrograph reported in Gaia DR2, we find FSR1758 has a radial velocity of 227 ± 1km s −1 . We also find potential extra-tidal star lost from the cluster in the surrounding 1 deg. Combined with Gaia proper motions and photometric distance estimates, this shows that FSR1758 is on a relatively retrograde, radial orbit with an pericen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
5
16
0
Order By: Relevance
“…2. These include the extended globular cluster FSR1758 [94,95] -from which the arboreal moniker originates--as well as the anomalous ω Centauri, which has for many years been believed to have begun life as the nucleus of a dwarf galaxy [96]. These clusters may have all originally been part of the Sequoia galaxy.…”
Section: B the Shardsmentioning
confidence: 99%
“…2. These include the extended globular cluster FSR1758 [94,95] -from which the arboreal moniker originates--as well as the anomalous ω Centauri, which has for many years been believed to have begun life as the nucleus of a dwarf galaxy [96]. These clusters may have all originally been part of the Sequoia galaxy.…”
Section: B the Shardsmentioning
confidence: 99%
“…Note that the eccentricity of the GC orbits cannot be constrained at present from available observations alone in a model-independent manner. The uncertainties in the observed parameters depend on the inherent assumptions in modeling the underlying potential (Simpson 2019). With better data, when the eccentricity distribution is more constrained, this analysis can be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…All of this evidence supports the genuine GC nature of FSR 1758, and not the hypothesis that this is the remnant nucleus of a dwarf galaxy. However, the dynamical properties of FSR 1758 reveal that it is not a cluster that originated in the inner Galaxy, and on the contrary is a halo intruder which circulates throughout the bulge in a highly eccentric, radial, and retrograde orbital configuration (see, e.g., Simpson 2019;Villanova et al 2019;Yeh et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding its origin, several different scenarios have been proposed for FSR 1758. Simpson (2019), based on its retrograde orbit, claimed that it could be an accreted halo GC; Villanova et al (2019) argued that it is a genuine MW GC based on the above evidence; and Yeh et al (2020) also supports the idea that it is likely a halo GC formed inside the MW, as the highly eccentric and retrograde orbital configuration are not uncommon among in situ halo GCs (Massari et al 2019). On the other hand, Myeong et al (2019) suggested that it belongs to the remnant debris of an early accretion event in the Milky Way, likely associated with a massive dwarf galaxy, similar to accretion events suggested for other GCs (see, e.g., Myeong et al 2019;Kruijssen et al 2019).…”
Section: Introductionmentioning
confidence: 99%